Instructional Management Skills and Effectiveness of Physical Education Instructors in Higher Education Institutions in Cebu City, Philippines - Coronel, Hazel Socorro; Ferrater-Gimena, Judy Ann (JPAIR Institutional Research, 2017)
Teaching has become multiple jobs. It could be in myriad aspects and in harmony with the context of effectiveness and improvement course. It is concerned with a wider range of outcomes, social, and affective. The study determined the instructional management skills and level of effectiveness of the PE instructors of the three higher education institutions of Cebu City, Philippines. A total of 24 instructors coming from three selected institutions participated in the study. There were 14 instructors from the University A, seven instructors from University B, and three instructors from University C. The study utilized a descriptive research method. It uses a researcher-designed survey tool to gather data on the profile of physical education instructors; their instructional effectiveness as well their management skills. There was correlation analysis on the profile and instructional management skills and the level of effectiveness. The ratings of the PE instructors of the three universities on the instructional management skills and instructional effectiveness were very good. Age, gender, education, teaching experiences, and seminar had nothing to do with instructional management skills and effectiveness of the PE instructors. However, there was a significant relationship between their instructional management skills and their instructional effectiveness. The majority of the PE teachers of the three institutions were positive on the given support of the administration in the form of facilities, materials, and equipment. Multimedia resources should be enriched to upgrade learning in physical education.